A rare case report of one stage surgical treatment for left renal cell carcinoma with level IV intravenous tumor thrombus combined with severe coronary artery stenosis. Issue 19 (May 2018) - Wang, Zhenqing; Zhang, Keqin; Zhang, Hui; Sun, Dingqi; Li, Yong; Tan, Qi; Fu, Qiang
Abstract: Rationale: Renal cell carcinoma (RCC) exhibits a natural tendency to extend from the kidney into inferior vena cava (IVC) and growing into the right atrium is a rare complication. We report a 65-year-old patient with an RCC with intravascular extension through renal vein into the IVC and right atrial combined with severe coronary artery disease. This case has not been described in the literature and there is no treatment guideline for it. Patient concerns: A 65-year-old patient was admitted to our clinic with complaints of edema of both lower extremities. Diagnoses: On the basis of the magnetic resonance imaging scan and coronary angiography, we strongly suspected an RCC with intravascular extension through renal vein into the IVC and right atrial combined with severe coronary artery disease. Interventions: We performed open left radical nephrectomy, IVC, and right atrium thrombectomy under cardiopulmonary bypass and coronary artery bypass grafting on beating heart. Outcomes: The postoperative course was uneventful. The patient has been discharged from hospital. Lessons: Coexistence of severe coronary artery disease and RCC infiltrating inferior vena cava and right atrium rendered this operation as very high-risk procedure. We hope that our operational manners can prove the possibility of simultaneous difficult cardiac and urologic operation. The basic point of our report concerns the fact that the oncologic treatment was not delayed despite severe heart disease.